THE Perception Of High School Students About Mathematics Learning Educational Content In Tiktok Applications - Heni Pujiastuti; Uswatun Hasanah (Universitas Cokroaminoto Palopo, 2022)
Because of the present COVID-19 epidemic, the government must adopt a variety of initiatives to keep the learning process functioning in Indonesia. The Minister of Education and Culture has created a policy on online learning systems to prevent the increase in COVID-19 cases. Educators employ a variety of educational material in online learning, such as the Tiktok application. On the Tiktok app, educational content is abundant, covering a wide range of topics, including mathematics. The purpose of this study is to observe how students react to math education content on the TikTok app. This research uses a qualitative descriptive method, using a questionnaire distributed via Google Forms. Six students from class X majoring in Mathematics and Natural Sciences at SMAN 1 Cilegon Banten were used as samples in this study. According to the findings, 83.3% of students utilized TikTok, and pupils found the mathematics instruction content in the TikTok program to be quite beneficial. As a medium for teaching mathematics to pupils, Tiktok instructional material offers several pros and problems. As a result, it is envisaged that TikTok will become a new type of educational material that educators may employ in the classroom.